Prognostic significance of metastatic lymph node ratio in patients with pN3 gastric cancer who underwent curative gastrectom - Bilici, Ahmet; Biricik, Fatih Selçuk; Şeker, Mesut; Öven, Başak Bala; Ölmez, Ömer Fatih; Yıldız, Özcan; Ölmüşçelik, Oktay; Hamdard, Jamshid; Açıkgöz, Özgür; Çakır, Aslı; Kapran, Yersu; Balık, Emre; et al. (Karger, 2019)
Background: Lymph node involvement is an important prognostic factor in patients with gastric cancer. The aim of this study was to determine the prognostic significance of metastatic lymph node ratio (MLNR) and compare it to the number of lymph node metastasis in pN3 gastric cancer. Methods: We retrospectively analyzed 207 patients with pN3 gastric cancer who had undergone radical gastrectomy. Prognostic factors and MLNR were evaluated by univariate and multivariate analysis. Results: An MLNR of 0.75 was found to be the best cut-off value to determine the prognosis of patients with pN3 gastric cancer (p = 0.001). The MLNR was significantly higher in patients with large-sized and undifferentiated tumors, vascular, lymphatic and perineural invasion, and total gastrectomy. In multivariate analysis, MLNR (p = 0.041), tumor differentiation (p = 0.046), and vascular invasion (p = 0.012) were found to be independent prognos-tic factors for disease-free survival, while both MLNR (p <0.001) and pN stage (p = 0.002) were independent prognostic indicators, as was tumor size, for overall survival. There was significant difference with respect to the recurrence patterns between MLNR groups. Lymph node and peritoneal recurrences were significantly higher in patients with MLNR> 0.75 compared to the MLNR <0.75 group (p <0.05). However, recurrence patterns were similar between pN3a and pN3b. Conclusion: Our results showed that MLNR was a useful indicator to determine the prognosis and recurrence patterns of patients with radically resected gastric cancer. Moreover, MLNR is a beneficial and reliable technique for evaluating lymph node metastasis.
WOS: 000464383800005
PubMed ID: 30870846
Keywords: Gastric Cancer; Metastatic Lymph Node Ratio; N3; Prognosis